On the Appropriateness and Necessity of Proofs and Proving in Middle School Mathematics Classrooms - Blair, Kevin (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Proofs are central to mathematics as a discipline, yet outside of high school geometry classes proofs and proving are often absent from school mathematics classes. The absence of proofs is detrimental to later student success in mathematics. Research indicates that proofs and proving, especially informal proofs, are appropriate for middle grades students and improve student understanding and confidence in their knowledge. This article discusses the research and calls for the inclusion of proofs and proving as a primary component of middle grades mathematics instruction.